HEART RHYTM DISORDERS AND THROMBOSIS. ANTICOAGULANT THERAPY OF CARDIAC ARRHYTHMIAS IN PREGNANCY - A. D. Makatsariya; S. V. Akinshina; V. O. Bitsadze (IRBIS LLC, 2016)
Heart rhythm disorders during pregnancy sifnificantly increase the risk of the cardioembolism in terms of the hypercoaguability state of pregnant women. The presence of atrial fibrillation during pregnancy in conditions of additional risk factors, inculding history of stroke and thromboembolic attacks, artifial heart valves, arterial hypertension, diabetes mellitus, ischemic disease or heart failure require anticoagulant therapy during all pregnancy. Acquired or genetic forms of thrombophilia also can increase the risk of thromboembolism in women with cardiac arrhythmias during pregnancy.